Between Ecology and Economy: Environmental Governance in India - Bedajna, Sutirtha (New Subjects and New Governance in India, 2012)
With the advent of neoliberalism, the discourse on governance has taken an interesting turn to further introspection in a changing world. The world, facing the opportunities and challenges of liberalisation, urges good governance, which has been defined by the World Bank through four key elements: (a) public sector management; (b) accountability; (c) legal framework for development; and (d) information and transparency. 1 All these are assumed as prerequisites for sound socio-economic development. In a resource-oriented, globalised, liberal world, governance is projected as perhaps the most appropriate device to confront and mitigate the challenges of the network society. 2 The World Bank has defined good governance in the following manner: 'Good governance is epitomised by predictable, open and enlightened policy making, a bureaucracy imbued with a professional ethos acting in furtherance of the public good, the rule of law, transparent processes and a strong civil society participating in public affairs.' 3 Governance is also articulated by the United Nations Development Programme (UNDP) in terms of eight major imperatives. They are participation, rule of law, transparency, responsiveness, consensus-orientation, equity and inclusiveness, effectiveness and efficiency, and accountability. Participation means informed and organised involvement either directly or through legitimate intermediate institutions or representatives. Rule of law urges fair legal frameworks that can be enforced impartially with full protection of human rights, particularly those of minorities. The freely and directly available information to those who will be affected by the process of governing and enforcement is the criterion of transparency. By being responsive, governance can gain legitimacy and effectiveness in the public domain. Good governance is expected to reach a broad consensus on issues that are in the best interest of the whole community in spite of the existence of different interest groups and voices in society. All the members of a society should feel included in the mainstream and should have an opportunity to improve or maintain their well-being. Efficiency addresses the best and sustainable use of natural resources and protection of the environment. And on the whole, accountability is the key factor of good governance. 4